In vitro effects of Er: YAG laser-activated photodynamic therapy on Enterococcus faecalis in root canal treatment - Guofeng Yang; Weiting Chen (Photodiagnosis and Photodynamic Therapy)
Objective: Photodynamic therapy (PDT) plays an important role for root canal disinfection. Nevertheless, the effect of photosensitizers penetrating dentin tubules is limited, which ultimately impedes the disinfection effect of PDT. The study implements an Er: YAG laser to activate methylene blue, the photosensitizer, to determine the bactericidal impact of PDT on Enterococcus faecalis in vitro root canals. Methods: We obtained 53 single root canal teeth with intact roots, standardized the root to 9 mm. The root canals were prepared using ProTaper rotary files. Subsequently, the teeth were sterilized, and Enterococcus faecalis was cultured for 3 weeks in vitro using brain heart infusion (BHI). The model of Enterococcus faecalis root canal infection of teeth was constructed by observing Enterococcus faecalis through electron microscope scanning. The teeth were randomly allocated to five treatment groups (n = 10): control, NaOCl, NaOCl + Er: YAG, PDT, and PDT + Er: YAG. Following treatment, the number of colony forming units (CFU)/ml was assessed for each group. Statistical analysis was conducted using one-way ANOVA, with post-hoc analysis using Tukey's test for multiple comparisons. Results: The colony counts in the remaining groups were significantly lower compared to the control group (P<0.001). Using PDT alone had the least impact on reducing colonies, while using PDT and Er: YAG laser together resulted in a significant reduction in colony counts (P<0.001). There was no significant difference in colony counts reduction between the NaOCl + Er: YAG group and the PDT + Er: YAG group (P = 1.000). Conclusions: The combination of Er: YAG laser and PDT significantly enhanced the bactericidal efficacy of PDT against Enterococcus faecalis in root canals. It had a similar impact on eliminating Enterococcus faecalis when compared to the effect of using Er: YAG laser and NaOCl.